Optimum crossing cable system in multi-span cable-stayed bridges. (1st April 2018) - Cid, C.; Baldomir, A.; Hernández, S.
Highlights: Optimum cable system in multi-span cable-stayed bridges with crossing cables. The number of cables is considered as design variable in the optimization process. Different number of cables each side of the same tower are allowed. Each cable anchor position on deck is associated to an independent design variable. Abstract: This paper presents a strategy to optimize the cable system of multi-span cable-stayed bridges with crossing stay cables. A general approach to minimize the steel volume in cables is performed considering number of cables, cable anchor positions on the deck, cable area and prestressing forces as design variables. Each cable anchor position is associated to an independent design variable allowing overlapping stay cables as well as different spacing along the deck. As the number of cables can vary throughout the bridge, the final design could have different number of cables on each side of the same tower. The possibility of designing a non-conventional cable arrangement leads to significant reductions in cable steel while satisfying structural design constraints. The Queensferry Crossing (UK) was chosen as a real application example to verify the capabilities of the proposed methodology.